RESEARCH ON THE INFLUENCE OF DIFFERENT TYPES OF ANION-EXCHANGE CARTRIDGES ON THE QUALITY OF [18F]NAF RADIOPHARMACEUTICAL AS PART OF PRODUCTION PROCESS DEVELOPMENT - Atanasova Lazareva, Marija; Ugrinska, Ana; Janevikj Ivanovska, Emilija (Institute of Knowledge Management (Publications), 2022)
[18F]Sodium Fluoride radiopharmaceutical is a sterile solution for intravenous administration, intended for skeletal visualization by positron emission tomography (PET). [18F]Sodium Fluoride for bone imaging was introduced in early 1960's, but with the increased availability of PET scanners in the last two decades, this radiopharmaceutical has growing use in clinical practice for the detection of bone metastases. The production process of [18F] NaF includes production of the radioisotope [18F]F- and purification and formulation of the [18F]NaF radiopharmaceutical. The radioisotope [18F]F- is produced by a cyclotron via the 18O(p,n)18F nuclear reaction, followed by recovery of [18F]F- from [18O] proton-irradiated water by adsorption and desorption from anion exchange resins. The fluoride anions are trapped on the anion-exchange SPE (solid-phase extraction) cartridge, and all other cationic and water-soluble radionuclide impurities present in irradiated enriched water are collected in the waste vial. Next step is desorption of the fluoride anions from the cartridge by elution with saline solution (0.9%NaCl). This study aimed to define the most appropriate type of anion-exchange SPE cartridge which could be used for routine production [18F]Sodium fluoride radiopharmaceutical which meets the quality requirements defined in European pharmacopeia monograph. For that purpose, as part of development of in-house production method, manual productions with four different types of anion-exchange cartridges were performed. The influence of sorbent substrate and counter-ion of the cartridge on the final yield and the quality of the produced radiopharmaceutical was investigated. The study also aimed to define the minimum volume of physiological solution required for the pH parameter to be within limits. The results have shown that the quality parameters: appearance, chemical purity, radiochemical purity and radionuclide purity were in defined acceptance criteria and did not differ when using different anion-exchange cartridges. The pH analyses have demonstrated that the type of cartridge and counter-ion influence the final pH of[18F]NaF solution. This study confirmed that the three types of anion-exchange resins (QMA-Cl-, QMA-CO32- and PS-OH-) could be used for production. In the experiments where QMA-Cl- was used, the required pH level was obtained even without dilution. The other cartridges could be used in the [18F] NaF production process, but further dilution is necessary in order to obtain the pH value in acceptance criteria. On the basis of this study, the QMA-Cl- is chosen as a cartridge to be used in the further development of the in-house method for [18F] NaF radiopharmaceutical production.
Keywords: [18F]Sodium fluoride; anion-exchange cartridges; pH; quality